The relationship between cognitive and affective control and symptoms of depression and anxiety across the lifespan: A 3-wave longitudinal study - Anson Kai Chun Chau; Savannah Minihan; Sakiko Okayama; Susanne Schweizer (Comprehensive Psychiatry)
Introduction: The association between cognitive functioning and mental health symptoms across the lifespan remains poorly understood. Understanding the directionality of the association between mental health and cognition is important as most gold-standard psychological therapies, such as cognitive-behaviour therapy, are cognitively demanding. Here, we examined the directionality of the association between cognitive and affective control with symptoms of depression and anxiety across the lifespan. Methods: 1002 participants (87.2 % female, age range: 11–89 years) completed self-report measures of depressive and anxiety symptoms and an affective backward digit span task thrice at 3-month intervals. Cross-lagged panel models (CLPMs) were used to model the longitudinal relationships between affective and cognitive control with depressive and anxiety symptoms. Multiple-group CLPMs were applied to test the model invariance between adolescents and adults. Results: The results supported a unidirectional relationship, where symptoms of depression and anxiety predicted impaired affective control across time points, over and above cognitive control. There was no evidence for affective or cognitive control capacity predicting emotional disorder symptomatology. In addition, multiple-group analysis revealed that depressive symptoms also predicted impaired cognitive control among adolescents only. There were no age-related differences in the associations between cognitive and affective control with anxiety symptoms. Conclusions: Our findings support depression and anxiety as antecedents, but not consequences, of impaired affective control. This suggests that timely management of emotional disorders, in particular for adolescents, is essential to prevent deterioration in cognitive functioning. The results further signal that practitioners should consider impaired affective control capacity in therapeutic contexts.